Penyelesaian Sengketa Tanah Ulayat Petuanan Mandesi Masyarakat Hukum Adat Maluku (Studi Putusan Nomor 50/Pdt.G/2021/Pn Sml.) - anasilviana; triyono; rindielvani (Jurnal Ragam Pengabdian, 2026)
his study examines the resolution of disputes and ownership of petuanan customary land within the Indigenous Law Community of Maluku, including the procedures for transferring rights over such land. It also analyzes judicial considerations in the Mandesi Petuanan Customary Land dispute as decided in case number 50/Pdt.G/2021/PN Sml. Using a normative juridical method, the research draws on legislation, court decisions, legal journals, and relevant literature, analyzed qualitatively. The findings indicate that the transfer of petuanan land ownership to parties outside the indigenous community is invalid without prior notification and consent from all relevant clan members. Any transfer of rights must also comply with Indonesian national law, particularly Maluku Provincial Regulation No. 3 of 2008 on Petuanan Areas. In the examined case, the court held that the plaintiff was a legitimate heir to the Mandesi Petuanan land but emphasized that dispute resolution must involve all authorized clan members. The judges concluded that no decision concerning customary land can be made without collective deliberation among the clan. The court further determined that the plaintiff had committed an unlawful act by transferring land rights without the knowledge and approval of other parties who were equally entitled to control and manage the customary land.